Utfordringar med to norske målformer i ISLEX - Rauset, Margunn (Nordiske Studier i Leksikografi, 2010)
This article takes ISLEX as its starting point. ISLEX is an online dictionary of 50,000 Icelandic words translated into Swedish, Norwegian and Danish. The dictionary is a joint project of four academic institutes in the Nordic countries: The Árni Magnússon Institute for Icelandic Studies in Reykjavík, The Society for Danish Language and Literature in Copenhagen, the Department of Linguistic, Literary and Aesthetic Studies at the University of Bergen and the Department of Swedish at the University of Gothenburg. I will focus on the challenges we face making an Icelandic-Norwegian dictionary that contains both language forms of Norwegian, Bokmål and Nynorsk. This means that we do not only have to consider equivalence between the source language and the target language, but also internally between the two Norwegian language forms. In most cases they are quite similar, but when it comes to phraseology it is our experience that they differ the most. Often it is harder to find equivalents to fixed expressions in Nynorsk than Bokmål. I will look at some examples which illustrate this and suggest some historical reasons why this is so.